Interferometric measurements of refractive index and dispersion at high pressure - Yong-Jae Kim (Nature Portfolio, 2021)
Abstract We describe a high precision interferometer system to measure the pressure dependence of the refractive index and its dispersion in the diamond anvil cell (DAC). The reflective Fabry–Perot fringe patterns created by both a white light and a monochromatic beam are recorded to determine both the sample thickness and its index at the laser wavelength and to characterize the dispersion in the visible range. Advances in sample preparation, optical setup, and data analysis enable us to achieve $$10^{-4}$$ 10 - 4 random uncertainty, demonstrated with an air sample, a factor of five improvement over the best previous DAC measurement. New data on $${\text{H}}_{2}\text{O}$$ H 2 O liquid water and ice VI up to 2.21 GPa at room temperature illustrate how higher precision measurements of the index and its optical dispersion open up new opportunities to reveal subtle changes in the electronic structure of water at high pressure.